EVALUATION OF NEOADJUVANT CHEMOTHERAPY RESPONSE IN PATIENTS WITH OVARIAN CANCER – MODERN ABILITIES OF MAGNETIC RESONANCE IMAGING - A. D. Makatsariya (Акушерство, гинекология и репродукция, 2017)
The purpose – to evaluate the capability of the integrated magnetic resonance imaging (MRI) with diffusion sequences in the assessment of neoadjuvant chemotherapy treatment response of ovarian cancer.Materials and methods. 23 patients with disseminated stages of ovarian cancer underwent pelvic and abdominal MRI to clarify the tumor spread, the issue of neoadjuvant chemotherapy (NHT) and again after 1 and 3 courses in the evaluation of its effectiveness. MR-study was performed on a superconductive 1.5 T MRI, using protocol: T2-, stir, T1-, Dynamic 3D FS, DWI with b-factors 0,1000 m/mm2 , with an estimate value of the apparent diffusion coefficient (ADC). The evaluation of differences in size of the entities was performed in accordance with RECIST 1.1 criteria, parameter measured: ADC.Results. Сomparative assessment of ADC before and after treatment revealed significant increase after 3 courses of chemotherapy (p=0.008), improvement after 1 course in the primary tumor and differences in the ADC before and after treatment in the omental and the peritoneal implants are less pronounced and insignificant (R=0.89; 0.758; 0.695 respectively). Informativity in evaluation of residual tumor and the degree of therapeutic pathomorphosis MRI were: sensitivity 93.3%, specificity 84.6%, and accuracy 91.3%.Conclusions. Diffusion MRI has high informativity and reproducibility in determination of response to neoadjuvant chemotherapy in advanced ovarian cancer. A significant difference in the mean ADC values was obtained for the solid component of the primary tumors, suggesting greater sensitivity to neoadjuvant chemotherapeutic treatment.